The religion of nature: Evangelical perspectives on the environment - Laugrand, Frédéric; Oosten, Jarich (Études/Inuit/Studies, 2010)
AbstractIn this paper we examine recent developments in Evangelical movements among the Inuit of the Canadian Eastern Arctic. We focus especially on Canada Awakening Ministries (CAM) and show how it successfully integrates traditional Inuit ideas and values in a modern Christian perspective. We explore how elders are given a more prominent role in the “healing the land” rituals and how traditional elements are becoming part of a Christian context. We examine CAM’s critical views on radical environmentalist groups and argue that its support of traditional Inuit hunting values through “biblical environmentalism” is bound to strengthen its position in the North.